COMPANY SIZE MODERATES: THE EFFECT OF PROFITABILITY, LEVERAGE, AND CAPITAL INTENSITY ON TAX AVOIDANCE - Dwi Oktaviani; Dhea Ayu Aprilia; Rifska Febriyani; Hakim, Mohamad Zulman; Imam Hidayat; Budi Rohmansyah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to determine the effect of profitability, leverage and capital intensity on tax avoidance moderated by company size. The sample of this study was 60 property & real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2021 - 2023. The results of the study stated that profitability had no effect on tax avoidance, leverage had no effect on tax avoidance while capital intensity had an effect on tax avoidance, and the company size variable was able to moderate the capital intensity, and the company size variable was unable to moderate profitability and leverage variables on tax avoidance in property & real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023.